2011
DOI: 10.1117/1.3625247
|View full text |Cite
|
Sign up to set email alerts
|

Optical scattering coefficient estimated by optical coherence tomography correlates with collagen content in ovarian tissue

Abstract: Optical scattering coefficient from ex vivo unfixed normal and malignant ovarian tissue was quantitatively extracted by fitting optical coherence tomography (OCT) A-line signals to a single scattering model. 1097 average A-line measurements at a wavelength of 1310 nm were performed at 108 sites obtained from 18 ovaries. The average scattering coefficient obtained from the normal tissue group consisted of 833 measurements from 88 sites was 2.41 mm(-1) (± 0.59), while the average coefficient obtained from the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 11 publications
2
102
0
Order By: Relevance
“…However, other OCT studies found that low attenuation is correlated with low collagen content, in the case of agarose scaffolds [39] and ex vivo ovarian tissue [40], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 83%
“…However, other OCT studies found that low attenuation is correlated with low collagen content, in the case of agarose scaffolds [39] and ex vivo ovarian tissue [40], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 83%
“…The attenuation coefficient has been routinely extracted from OCT measurements based on Beer's law, which is appropriate for low NA measurements. This simple model has proven to be useful in detecting cancerous tissues in skin, bladder and brain [1][2][3], monitoring blood glucose concentration [4], characterizing atherosclerosis plaques [5,6] and correlating collagen content with histological staining [7]. Recently, quantification of the attenuation coefficient has been adopted in brain imaging [8] to follow neurological development in mouse models [9], to detect borders of brain tumors in human specimens [3,10], and to examine the physiological alterations in edema [11].…”
Section: Introductionmentioning
confidence: 99%
“…Optical properties have also been estimated in other tissues using OCT. Yang et al 35 determined the optical scattering coefficient, μ s , from unfixed normal and malignant, ex vivo ovarian tissues. They found that the absorption coefficient, μ a , for ovarian tissue is small (∼0.006 mm −1 ) and that μ t was a good approximation to μ s .…”
Section: Introductionmentioning
confidence: 99%